Tumor-Induced Myeloid-derived Suppressor Cell Function is Independent of IFNγ and IL-4Rα - Sinha, Pratima (2012)
Myeloid-derived suppressor cells (MDSC) are present in most cancer patients and experimental animals where they exert a profound immune suppression and are a significant obstacle to immunotherapy. IFNγ and IL-4Rα have been implicated as essential molecules for MDSC development and immunosuppressive function. If IFNγ and IL-4Rα are critical regulators of MDSC, then they are potential targets for preventing MDSC accumulation or inhibiting MDSC function. Because data supporting a role for IFNγ and IL-4Rα are not definitive, we have examined MDSC induced in IFNγ-deficient, IFNγR-deficient, and IL-4Rα-deficient mice carrying three C57BL/6-derived tumors (B16 melanoma, MC38 colon carcinoma, and 3LL lung adenocarcinoma), and three BALB/c-derived tumors (4T1 and TS/A mammary carcinomas, and CT26 colon carcinoma). We report that although MDSC express functional IFNγR and IL-4Rα, and have the potential to signal through the STAT1 and STAT6 pathways, respectively, neither IFNγ nor IL-4Rα impacts the phenotype, accumulation, or T cell suppressive potency of MDSC, although IFNγ and IL-4Rα modestly alter MDSC-macrophage IL-10 cross-talk. Therefore, neither IFNγ nor IL-4Rα is a key regulator of MDSC and thus targeting these molecules is unlikely to significantly alter MDSC accumulation or function.